Large perpendicular magnetic anisotropy in magnetostrictive Fe1-xGax thin films - Barturen, Mariana (2015)
In this work we report the appearance of a large perpendicular magnetic anisotropy (PMA) in Fe1−xGaxthin films grown onto ZnSe/GaAs(001). This arising anisotropy is related to the tetragonal metastable phasein as-grown samples recently reported [M. Eddrief et al., Phys. Rev. B 84, 161410 (2011)]. By means offerromagnetic resonance studies we measured PMA values up to ∼5 × 105 J/m3. PMA vanishes when the cubicstructure is recovered upon annealing at 300 ◦C. Despite the important values of the magnetoelastic constantsmeasured via the cantilever method, the consequent magnetoelastic contribution to PMA is not enough to explainthe observed anisotropy values in the distorted state. Ab initio calculations show that the chemical ordering playsa crucial role in the appearance of PMA. Through a phenomenological model we propose that an excess ofnext-nearest-neighbor Ga pairs (B2-like ordering) along the perpendicular direction arises as a possible source ofPMA in Fe1−xGax thin films.